An Analysis of Students’ Academic Record Using Data Mining Techniques and Identification of Key Factors to Aid Students’ Performance (GUB Journal of Science and Engineering, 2018)
With the improvement of information technology, presently educational institutions generally store and compile a huge volume of students’ data. This huge volume of data can be analyzed using different data mining techniques and extract hidden relation between students’ result with other academic attributes. The main objective of this paper is to evaluate the impact of different academic attributes on the students’ final result using data mining techniques. We used different data mining techniques to analyze students data collected from Green University of Bangladesh. We applied three well-known classification algorithms namely Decision Tree, Naïve Bayes, and SVM to develop a prediction model that can suggest probable grade by analyzing parameters like the midterm, attendance, assignment, presentation, class test, final, and CT marks. Our goal is to find out the key factors playing as a catalyst for getting good or bad CGPA. Through this research, the university authority will get the knowledge about key factors playing significant role in students’ result that will help them to take proper decisions to improve students’ grade that in turns will reduce students’ dropout.GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 5(1), Dec 2018 P 45-50